2016
DOI: 10.1002/anie.201512062
|View full text |Cite|
|
Sign up to set email alerts
|

A Click Chemistry‐Based Proteomic Approach Reveals that 1,2,4‐Trioxolane and Artemisinin Antimalarials Share a Common Protein Alkylation Profile

Abstract: In spite of the recent increase in endoperoxide antimalarials under development, it remains unclear if all these chemotypes share a common mechanism of action. This is important since it will influence cross‐resistance risks between the different classes. Here we investigate this proposition using novel clickable 1,2,4‐trioxolane activity based protein‐profiling probes (ABPPs). ABPPs with potent antimalarial activity were able to alkylate protein target(s) within the asexual erythrocytic stage of Plasmodium fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
79
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 25 publications
10
79
0
1
Order By: Relevance
“…First, Plasmodium parasites require the proteasome to progress through their complex lifecycle and a number of different classes of inhibitors have been shown to block growth or kill parasite at all lifecycle stages including the transmissive gametocyte stages [918]. Second, proteins damaged by indiscriminate protein alkylation caused by the antimalarial action of endoperoxides such as ART and the newer synthetic ozonides (OZ277, OZ439) that mimic artemisinin action [2224] must be degraded to maintain homeostasis. The proteasome carries the largest burden of protein degradation, and has been the best characterized of the various degradative systems in Plasmodium .…”
Section: Combating Drug-resistant Malaria: Upsetting the Proteostaticmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Plasmodium parasites require the proteasome to progress through their complex lifecycle and a number of different classes of inhibitors have been shown to block growth or kill parasite at all lifecycle stages including the transmissive gametocyte stages [918]. Second, proteins damaged by indiscriminate protein alkylation caused by the antimalarial action of endoperoxides such as ART and the newer synthetic ozonides (OZ277, OZ439) that mimic artemisinin action [2224] must be degraded to maintain homeostasis. The proteasome carries the largest burden of protein degradation, and has been the best characterized of the various degradative systems in Plasmodium .…”
Section: Combating Drug-resistant Malaria: Upsetting the Proteostaticmentioning
confidence: 99%
“…ART and synthetic ozonides alkylate proteins that are involved in a wide variety of cellular processes, including hemoglobin degradation, antioxidant responses, and stress pathways [2224]. Recent evidence suggests that ART-treated parasites accumulate ubiquitinated polypeptides [25], providing an increased load of proteins that require degradation.…”
Section: Combating Drug-resistant Malaria: Upsetting the Proteostaticmentioning
confidence: 99%
“…Understanding the mechanism of action of both the artemisinins and the ozonides is an active area of research. Various biochemical and biomimetic approaches have been utilized to identify both the molecular targets of peroxide antimalarials and parasite biochemical pathways perturbed in response to drug treatment (29,(39)(40)(41)(42). Many of these in vitro techniques require the use of specific conditions such as high parasitemia (39,40,42,43) for optimal assay performance, and these conditions differ considerably from those used in typical in vitro drug activity measurements.…”
mentioning
confidence: 99%
“…[4][5][6] Recently,i tw as shown that artemisinins are ligands of the mammalian protein gephyrin [7] and that the mechanism of action of these molecules depends on the enhancement of GABA-A receptor signaling,which leads to the regeneration of pancreatic bcells from a-cells in aR OS-independent manner.T herefore, artemisinins may also find application in the treatment of diabetes mellitus.I na ddition, Lisewski et al [8] reported that the Plasmodium falciparum antigen EXP1, am embrane glutathione S-transferase,i sp otently inhibited by artesunate in acompetitive mode.Despite all this,the exact nature of the mechanism and the molecular target, as well as whether the action of artemisinins is stereospecific,remain elusive and are still under debate. [9,10] Herein, we show that the antimalarial activity of artemisinin is not stereospecific,and ageneral and straightforward approach to this natural endoperoxide is presented that enables the synthesis of artemisinin derivatives that are not accessible by applying current methods.S everal proteins have been reported to be the targets of this sesquiterpene lactone.R ecently,i dentification of ap lethora of artemisinin-binding proteins of Plasmodium falciparum was reported by Wang et al [11,12] Similar studies were also carried out by Ismail et al [13] Therefore,t he hypothesis that artemisinin interacts with as pecific protein of Plasmodium falciparum is questionable as described by Fügi et al [14] Furthermore,a ccording to investigations of ONeill et al, artemisinin activity against this parasite is not stereospecific. [15] To unequivocally answer this question, investigation of the biological activity of (À)-artemisinin (1;t he antipode of natural (+ +)-artemisinin) is absolutely necessary.…”
mentioning
confidence: 77%